2021
DOI: 10.1101/2021.01.29.21250730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How best do we engage the general population in testing for COVID-19?

Abstract: The UK Scientific Advisory Group for Emergencies (SAGE) emphasises the need for high levels of engagement with communities and individuals to ensure the effectiveness of any COVID-19 testing programme. A novel pilot health surveillance programme to assess the feasibility of weekly mass RT-LAMP testing for the SARS-CoV-2 virus using saliva samples collected at home was developed and piloted by the University of Southampton and Southampton City Council. Rapid qualitative evaluation was conducted to explore exper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Another barrier was concern about taking a lateral flow test, which included the concerns that tests were being used to collect personal data, the potential health risks from the tests, discomfort of testing, and perception that taking a test twice a week was not normal and concerns over how long this would last. This is in-line with previous research that has identified concerns about use of personal data and discomfort of swabbing as barriers to testing [7,18].…”
Section: Barriers To Testingsupporting
confidence: 90%
See 2 more Smart Citations
“…Another barrier was concern about taking a lateral flow test, which included the concerns that tests were being used to collect personal data, the potential health risks from the tests, discomfort of testing, and perception that taking a test twice a week was not normal and concerns over how long this would last. This is in-line with previous research that has identified concerns about use of personal data and discomfort of swabbing as barriers to testing [7,18].…”
Section: Barriers To Testingsupporting
confidence: 90%
“…Lack of support for those self-isolating has also been identified as a barrier to testing in previous research [6,7], and therefore financial support should be provided to everyone who needs to self-isolate, in order to encourage uptake of testing [19].…”
Section: Barriers To Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative peer pressure was also a recurrent theme in studies involving student participants, since students are keenly aware that a positive test result will require peers (and often members of a shared household) to self-isolate [27,38]. Consistent with the above findings, a range of studies found that endorsements from and/or solidarity with peers, families, and supportive institutional cultures encourage testing [23,24,26,32,33]. This was especially true in institutional settings (e.g., schools and GP surgeries), where participants' decisions to engage in a pilot project were 'influenced by a pull on their sense of community' [24] (p. 9) and the feeling that they were 'in it together' [23] (p. 22) There is some ambiguity about the relative influence of negative and positive pressure in these studies, however, since participants were also reported to fear the stigma associated with a positive test result [24].…”
Section: Logistics Of Testingmentioning
confidence: 82%
“…4.1.4. Social Solidarity, Peer-Pressure, and Stigma Social pressure (e.g., relating to the expected reactions of employers, friends, and family to an individual's decision to seek testing or test result) was a sub-focus of 14 studies in this review [23,24,26,27,32,33,38,40,45,46,48,54,67]. Six studies focused on negative pressure from employers and peers [38,40,45,46] or stigma [54,67] as barriers to testing.…”
Section: Logistics Of Testingmentioning
confidence: 99%